The Effect Of Adding Coconut Drugs Flour (Coccus nucifera L) on Protein Levels of Apen Cakes - Jannah, Nur Roudatul; Hasanah, Alfiatul (Teknologi Hasil Pertanian, Fakultas Teknik, Universitas Annuqayah, 2024)
Coconut pulp is waste obtained from coconut milk production and contains quite complete nutrients. Coconut dregs can be processed into flour which can be produced into food products. Apen cake is a food whose processing uses rice flour which is rich in carbohydrates, but quite low in protein. Therefore, adding coconut dregs flour which is high in protein can be an alternative to further optimize the nutritional content of Apen cake. There are five treatments that will be studied to see the protein content in Apen cake, with the ratio of rice flour: coconut dregs flour as follows: P1 (100%: 0%), P2 (0%: 100%), P3 (75%: 25% ), P4 (50%:50%), and P5 (25%:75%). Research on protein content testing in Apen cake was carried out using the Kjeldahl method. The results of research using the Kjeldahl test stated that Apen cake with the addition of coconut dregs flour contains higher protein than Apen cake in general. Next, the results of the protein test were tabulated in one way ANOVA to determine whether there were differences between treatments or not. The data tabulation results show a sig value ≤ 0.05. Therefore, further BNT tests were carried out to find out which treatments were most significantly different. The results of the BNT further test stated that P5 was the treatment with the most significantly different samples, and had the most influence on the protein content of Apen cake